Pharmacological properties of Pomaria sandersonii, Pentanisia prunelloides and Alepidea amatymbica extracts using in vitro assays - Muleya, Eddwina; Ahmed, A. S.; Sipamla, A. M.; Mtunzi, F.M.; Mutatu, W. (Academic Journals, 2016)
The antimicrobial, anti-inflammatory and free radical scavenging activities of root crude acetone extracts and fractions of different polarities from Pomaria sandersonii (Fabaceae), Pentanisia prunelloides (Rubiaceae) and Alepidea amatymbica (Apiaceae) were determined using in vitro assays. The antioxidant properties of extracts and fractions were assessed by reduction of 2, 2´-azinobis (3-ethylbenzothiazoline)-6-sulfonic acid and 2, 2-di (4-tert-octylphenyl)-1-picrylhydrazyl radicals which was measured by changes in absorbance using an ultraviolet-visible spectrophotometer. Anti-inflammatory activity of the plant extracts against 15 soybean lipoxygenase enzyme was measured by monitoring the change in absorbance at 234 nm after incubation of 15-LOX with linoleic acid (134 µM) as substrate. The anti-microbial activities were determined by measuring the minimum inhibitory concentrations using a serial dilution microplate method with terazolium violet as a growth indicator. The minimal inhibitory concentration (MIC) value of the dichloromethane (DCM) and ethyl acetate fractions (1 mg/ml) of P. sandersonii was 80 µg/ml in each case against Staphylococcus aureus and Escherichia coli. The inhibition activity of 15 soybean lipoxygenase enzyme by the crude extracts at concentration of 25 μg/ml was 97% for P. sandersonii, 79% for P. prunelloides and 55% for A. amatymbica. This indicates that extracts for these plants can be used as dietary supplements in the management of inflammation related conditions.